2005
DOI: 10.1007/s00586-005-0905-7
|View full text |Cite
|
Sign up to set email alerts
|

Spondylitis following vertebroplasty: a case report

Abstract: Spondylitis is a rare complication of vertebroplasty. In the presented case a satisfactory result could be achieved through conservative antibiotic therapy and restriction of movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 27 publications
0
23
0
2
Order By: Relevance
“…Although low complication rates are characteristic of vertebral augmentation, evidence suggests that percutaneous vertebroplasty and kyphoplasty can be associated with subsequent spinal infection [4][5][6][7][8][9][10][11][12][13][14]. Furthermore, several cases of osteomyelitis occurring at the site of injury have been reported [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although low complication rates are characteristic of vertebral augmentation, evidence suggests that percutaneous vertebroplasty and kyphoplasty can be associated with subsequent spinal infection [4][5][6][7][8][9][10][11][12][13][14]. Furthermore, several cases of osteomyelitis occurring at the site of injury have been reported [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Schmid et al 20 reported a 55-year-old man with previous medical history of liver cirrhosis who developed spondylitis after three lumbar vertebroplasties. A paravertebral abscess was aspirated without bacteria identification.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In most of these reported cases, a specific infectious agent was not identified. The bacteria isolated in other reports were Serratia marcescens, Stenothrophomonas maltophilia, Burkholderia cepacia, and Streptococcus agalactiae.…”
Section: Infectious Complications Reported In Vertebroplastymentioning
confidence: 99%
“…Fortunately, the reported rate of localized infection of the implant is rare, with fewer than 10 reported cases. [1][2][3][4][5] The ramifications of such infection are severe because clearance of the infection without vertebrectomy would be unlikely. Efforts to avoid cement infection have been previously described in the vertebroplasty literature, including routine use of either systemic or local infusion of prophylactic antibiotics as well as exclusion of pre-existing infections either in the target vertebral body or elsewhere.…”
mentioning
confidence: 99%